2010
DOI: 10.1172/jci41678
|View full text |Cite
|
Sign up to set email alerts
|

Heat generates oxidized linoleic acid metabolites that activate TRPV1 and produce pain in rodents

Abstract: The transient receptor potential vanilloid 1 (TRPV1) channel is the principal detector of noxious heat in the peripheral nervous system. TRPV1 is expressed in many nociceptors and is involved in heat-induced hyperalgesia and thermoregulation. The precise mechanism or mechanisms mediating the thermal sensitivity of TRPV1 are unknown. Here, we have shown that the oxidized linoleic acid metabolites 9-and 13-hydroxyoctadecadienoic acid (9-and 13-HODE) are formed in mouse and rat skin biopsies by exposure to noxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
216
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(225 citation statements)
references
References 37 publications
6
216
2
1
Order By: Relevance
“…Now linoleic acid, an essential -6 fatty acid precursor of arachidonic acid and a major membrane constituent of mammalian cells, has been found to have a related role. Hargreaves and colleagues (1) have shown that oxidized linoleic acid products produced from heated skin are potent activators of TRPV1, the capsaicin receptor, which plays a major role in thermal hyperalgesia. They make a strong case that these mediators contribute substantially to heat-activated TRPV1 currents in sensory neurons.…”
Section: Fat Location Defines Sensationmentioning
confidence: 99%
“…Now linoleic acid, an essential -6 fatty acid precursor of arachidonic acid and a major membrane constituent of mammalian cells, has been found to have a related role. Hargreaves and colleagues (1) have shown that oxidized linoleic acid products produced from heated skin are potent activators of TRPV1, the capsaicin receptor, which plays a major role in thermal hyperalgesia. They make a strong case that these mediators contribute substantially to heat-activated TRPV1 currents in sensory neurons.…”
Section: Fat Location Defines Sensationmentioning
confidence: 99%
“…Extravasation into peripheral tissues can be induced by activating transient receptor potential vanilloid-1 (TRPV1), a prominent member of the TRP ion channel superfamily (10). TRPV1 is expressed on the major subset of sensory afferent neurons that integrate noxious stimuli including heat and acidity (11)(12)(13). The outcome of peripheral TRPV1 activation and consequent cation influx in TRPV1 + sensory neuron is two-fold; (i) electric afferent signal transduction to the CNS, generating pain perception and (ii), local efferent release of neuropeptides such as substance P (sP) and calcitonin generelated peptide (CGRP) …”
Section: Introductionmentioning
confidence: 99%
“…anandamide, arachidonic acid metabolites such as N-arachidonoyl-dopamine [NADA], 12-hydroperoxyeicosatetraenoic acid, oxidized linoleic acid metabolites, essential oils, octadecadienoids), and a variety of pungent plant products as exemplified by capsaicin (responsible for the piquancy of hot chilli peppers), resiniferatoxin, piperine (the pungent ingredient in black pepper), gingerol and zingerone (from ginger), camphor, as well as eugenol (a powerful essential oil found in cloves). Interestingly (and somewhat unexpectedly), TRPV1 is also activated by ethanol and venoms from jellyfish and spiders [9,[40][41][42][43][44][45][46][47][48][49].…”
Section: Trpv1 As Polymodal Sensor Expressed On Peptidergic Sensory Nmentioning
confidence: 93%